Comparison of Granisetron and Dexamethasone in management of post operative nausea and vomiting (PONV) in laparoscopic gynaecological surgery - Begum, Kawser; Rahman, Rezwanur; Habibullah, AKM; Ali, Md Younus; Ibrahim, Kamal; Banik, Debabrata (Journal of the Bangladesh Society of Anaesthesiologists, 2020)
Background: Postoperative nausea and vomiting (PONV) is a common problem. It is more common inlaparoscopic surgery than in open surgery and following laparoscopic gynaecological surgery. PONVcauses patient discomfort and can prolong the time of hospital discharge.It causes potential hospitalburden and loss of unanticipated working time both for the patients and doctors. Management of thisproblem based on prevention rather than treatment. Various antiemetic drugs including steroids areeffective in the prevention of PONV but which one is better still now a debateable one. On the basis of thisfact there were numerous research, articles, analysis and publication work done all over the world. Objectives: Comparison of granisetron and dexamethasone to detect which one is better in managementof PONV after laparoscopic surgery. Method: The patient were selected after ethical committee approval. After informed written consent wehave selected 100 ASA- I & II patients undergoing general anaesthesia for laparoscopic gynaecologicalsurgery in a prospective double blind randomized study. Patients who had received opoids, NSAIDS,steroids or antiemetic agent before previous 4 weeks or who has known hypersensitivity to granisetron ordexamethasone. Patients were divided as group-A (granisetron) and Group-B(dexamethasone). 50 patientwere member of each group. Every patient got study drug during induction. Group-A got granisetron andgroup-B got dexamethasone for prevention of PONV. There were no differences in background factors orfactors related to anaesthesia, analgesics consumption, pain or side effects between groups. The data collectedin a fixed protocol form from the patient consented for the study. After collection of data were coded, edited,compiled and entered into computer system for analysis. The result will help to guide the anaesthesiologistspracticing in the third world countries like Bangladesh in the management of PONV. Results: The current study showed the intravenous injection of 8 mg dexamethasone, or 3 mg Granisetronhave similar effects on PONV prophylaxis in laparoscopic gynaecological surgery. These results of thecurrent study indicated that Dexamethasone is a suitable substitute for Granisetron. Conclusion: Dexamethasone and Granisetron are comparable in management of PONV. These drugsinjection before anesthesia induction have similar effects on nausea and vomiting prophylaxis afterlaparoscopic gynaecological surgery. Prophylactic use of dexamethasone should be routine to preventPONV because dexamethasone is cost effective than granisetron. JBSA 2020; 33(1): 36-42